41 - PHYSICAL EXERCISE’S EFFECT ON MEMORY-RELATED NEUROBIOLOGICAL IMPAIRMENTS OF ALZHEIMER’S DISEASE (Fiep Bulletin - online, 2023)
Introduction: The most prevalent symptom related to the Alzheimer’s disease (AD) is the impairment in the Working Memory (WM), and the physical exercise display effectiveness, although, limited. Objective: To investigate the effect of physical exercise (PE) on working memory of older adults with memory impairment due to Alzheimer’s disease. Methods: Forty- four subjects, all with Alzheimer’s disease diagnose were divided into two groups (CG) that received only classical treatment, and Exercise Intervention Group (EIG) that received physical exercise plus classical treatment. The working memory was investigated before and after three months of intervention. The statistical procedure was conducted by Kruskal-Wallis with DUNN’S post hoc test, with a significance level of 5%. Results: The CG group display decrease in the WM, however, and EIG showed increasing in the WM performance. Conclusion: PE improves the WM of older adults with memory impairment due to Alzheimer’s disease.
Keywords: Alzheimer’s Disease; Classical Treatment; Physical Exercise Intervention. Older Adults.